Supplier Evaluation Schemes in Case of Different Research Frameworks - Pató Gáborné Szűcs , Beáta; Kiss, Fanni (International Journal of Engineering and Management Sciences, 2020)
Performance evaluation is not only important in employer and employee relationships, but also in partnerships between a supply chain’s members. In order to satisfy customers’ needs according to the 7 Rights of logistics, all members of the given chain have to perform properly. To ensure the best performance, supplier evaluation can act as a starting point. Besides continous feedback, supplier evaluation plays an important role in performance development of suppliers. The aim of our research is to develop and introduce innovative supplier evaluation models, which include the advantages of traditional and electronic supplier evaluation forms. In addition to this, these models are visualised, making it easier to understand expectations and information. In this study, the aim is to present two different models the PaTeNt©- SESC (Pató Tetrahedrons of interNational Theory - Supplier Evaluation of Supply Chain) and the Douple Evaluation Platform, based on previous research.